Intervención en el diseño de recursos para la ejecución de terapias de estimulación cognitiva en casa para adultos mayores pacientes de Alzheimer. (2022)
Alzheimer's disease is the most common neurocognitive disorder and the seventh most common cause of death globally, in addition, Alzheimer's disease represents the most common and dangerous disease for people over 60 years of age.It is estimated that around 50 million people worldwide suffer from some type of dementia and of which 60% live in low-and middle-income countries, additionally each yearan estimated 10 million new cases are recorded. During the year 2020 in Colombia, it was estimated that around 5.2% of the population over 60years of age suffered from some major neurocognitive disorderand 70% of these suffer from Alzheimer's or other diseases that cause memory loss or impairment.There are no curative or modifying treatments for this disease,so it must be controlled through pharmaceuticaltreatment and cognitive therapy; Additionally, movement difficulties and limitations are commonly founded in elderly people, that often, don’t have the means necessary to accessspecialized centers in order to receive cognitive therapy treatments.On par with this and aside from the lack of awareness and information regarding this disorder, there is a lack of tools and resources that help elderly patients, their families,and caretakers to executecognitive therapy from their homes, this project aims to generate home resources that provide cognitive stimuli and support for Alzheimer patients and their close circle in order to perform integral therapy from their home.